Voltammetric studies of selected porphyrin G-quadruplex ligands and their interaction with DNA in solution and at the mercury electrode surface. (20th October 2021) - Dobrovodsky, Daniel; Danhel, Ales; Mothes-Martin, Emmanuelle; Pratviel, Genevieve; Mergny, Jean-Louis; Fojta, Miroslav
Abstract: With the increasing interest in DNA G-quadruplexes (G4) as important regulatory elements and prospective therapeutical targets, DNA structure-sensitive electrochemical methods can be advantageously used for studying of their structure or screening for interactions with G4 ligands developed as candidate drugs. Porphyrin derivatives are among the most prominent classes of G4 ligands. Interactions of porphyrins H2 -TMPy2PP and Cu-TMPy2PP with oligodeoxynucleotides (ODNs) either forming or not forming G4 were investigated in this work. For this purpose, cyclic voltammetry at hanging mercury drop electrode (HMDE) complemented by UV-vis and CD spectroscopy was applied. Both porphyrins were found to interact strongly with G4 in solution by UV-vis titrations. However, Cu-TMPy2PP appears to interact also with double-stranded and single-stranded ODNs. Accordingly, cyclic voltammetry was able to distinguish between free and ODN-bound forms of Cu-TMPy2PP, but not between binding of the ligand to ODNs with or without G4 propensity.